Do sectors (still) matter? Exploring similarities and differences between public, private, and non-profit organizations from an organizational identity perspective - Nunes, F. G.; Nascimento, G. do.; Martins, L. D. (Nonprofit Management and Leadership, 2024)
This paper uses an organizational identity perspective to investigate similarities and differences between public, private and nonprofit organizations. The analysis is focused on three interrelated identity domains: the content used by members to define their organizations; the orientation of the organizational identity (individualistic, relational, and collectivistic); the nature of members’ attachment to their organizations (identification, neutral identification, ambivalent identification, disidentification). Using a sample of 256 members of organizations belonging to these three sectors we found that: the content used to describe public, private and nonprofit organizations, although sharing numerous elements, also contains sector-specific meanings especially in nonprofit organizations; concerning the organizational identity orientation, private organizations are seen as more individualistic and more relational than public and nonprofit ones, while public organizations score high in the collectivistic orientation; regarding the nature of members’ attachment, although members of the three types of organizations exhibit the same levels of organizational identification and neutral identification, nonprofit organizations generate more disidentification and ambivalent identification among their members than public and private ones. Overall, organizational elements revealing operational practices tend to be similar, while those elements representing organizational identity tend to be different.